A non-destructive single plate method for measurement of thermal resistance of polymer sheets and fabrics. Issue 4 (2nd October 2019) - Dolezal, Ivan; Hes, Lubos; Bal, Kausik
Abstract : Measurement of thermal resistance of polymer sheets and fibrous layers is important in various applications including those within the engineering, ergonomics, clothing design and personal protective equipment fields. Standard methods for measurement of thermal resistance of plain materials are generally time consuming, expensive and often require the sample to be cut. Moreover, the temperature difference between the surfaces of both plates surrounding the sample must be known, as well as the sample thickness. This article describes a new measuring device named the Thermoscope. The Thermoscope is not limited by the aforementioned requirements and is able to evaluate the thermal resistance of polymer sheets and textiles by touching the sample on one surface alone. Simultaneously, the other surface is kept in thermal contact with the supporting base. The accuracy of this device was compared with the Alambeta thermal insulation tester. Effects of various base materials on measurement precision were also studied.